Subcutaneous Angiolipoma of the Forearm- A Distinct Rare Entity of a Common Variant - Monal Trisal; Safia Rana; Nehal Ahmed; Sujata Jetley (Dr. Annil Mahajan, 2022)
Lipomas are commonest benign mesenchymal neoplasms. Angiolipoma is a rare variant of usual lipomas characterized by adipocytes and vascular channels most frequently arising in the lower extremity. We report a rare case of a young male presenting with multiple deep painful nodules over the mid forearm which on histopathological examination revealed encapsulated benign tumour comprising of proliferating small-calibre vascular channels with microthrombi and mature adipose tissue.